Survey Says…?: Assessing Interlibrary Loan/Document Delivery Use and Awareness for Responsive Service Delivery. Issue 5 (20th October 2019) - Yang, Zheng Ye (Lan); Goodwin, Susan G.; Hahn, Doug
Abstract: The object of this study is to assess Texas A&M University (TAMU) students/faculty/staff members' use and awareness of the Libraries' free document delivery and interlibrary loan service, branded as "Get It For Me." Since 2010, we have continued to see a decline in new user registrations each year. Previous Get It For Me user surveys conducted in 2003 and 2011 indicated that the overall satisfaction of registered users was high and customer feedback gleaned from these surveys was used to initiate a number of service improvements. But what about the large percentage of the campus community who do not use the Get It For Me service? Are they aware of what this service has to offer? If so, why might they choose not to use it? If they are not aware of the service, might they use it if they knew more about how it can assist them in their scholarly endeavors? Instead of only surveying those customers who have used this service, we invited everyone on TAMU College Station campus to participate in the survey. Promoting the service is a vital component of service delivery.